Digital accessibility on institutional websites of Portuguese tourism - Silva, Maria de Fátima (2020)
In this chapter we address the problem of accessibility and accessible tourism concerning the various types of information and communication, namely, the digital information resulting from technological innovation implemented in recent years in various websites. Aswehavebeendevelopingstudiesontheimpactsofaccessibilityandaccessible tourism, we consider it fundamental to analyse the compliance of Portuguese institutional sites in the tourism area with the new European directives and Portuguese legislation. In this sense, the main objective of this chapter is to understand how the institutional Web content related to Portuguese tourism meets the accessibility requirements of the Web Content Accessibility Guidelines 2.0 (WCAG 2.0), of the World Wide Web Consortium (W3C). The sample reﬂects the Portuguese panorama of institutional websites related to Portuguese tourism activity and promotion.Overall,with respect to accessibility practices, itis possible to conclude that none of the websites analysed meets the compliance levels of WCAG 2.0. The results point to an inequality in the dynamics and development of the Portuguese territory.